2005
DOI: 10.1111/j.1365-294x.2005.02657.x
|View full text |Cite
|
Sign up to set email alerts
|

Migratory charr schools exhibit population and kin associations beyond juvenile stages

Abstract: Few studies have critically investigated the genetic composition of wild fish schools. Yet, such investigations may have profound implications for the understanding of social organization and population differentiation in both fundamental and applied research. Using 20 microsatellite loci, we investigated the composition of 53 schools (total n = 211) of adult and subadult migratory brook charr (Salvelinus fontinalis) sampled from the known feeding areas of two populations inhabiting Mistassini Lake (Québec, Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 92 publications
(167 reference statements)
2
63
1
Order By: Relevance
“…Evidence for kin-structured free-ranging fish shoals has been obtained for a few species (Ward & Hart 2003, Piyapong et al 2010. Migratory charr Salvelinus fontinalis were found to have kin-structured subgroups with associations predicted to last for up to several years (Fraser et al 2005). Several other studies have demonstrated that fish are capable of kin recognition (Olsen 1989, Gerlach & Lysiak 2006.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Evidence for kin-structured free-ranging fish shoals has been obtained for a few species (Ward & Hart 2003, Piyapong et al 2010. Migratory charr Salvelinus fontinalis were found to have kin-structured subgroups with associations predicted to last for up to several years (Fraser et al 2005). Several other studies have demonstrated that fish are capable of kin recognition (Olsen 1989, Gerlach & Lysiak 2006.…”
Section: Discussionmentioning
confidence: 97%
“…Kin-structured social groups have previously been documented for a range of taxa (Parsons et al 2003, Fraser et al 2005. However, as far as we know, the question of whether sharks avoid or preferentially associate with kin has been completely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…First, substantial evidence indicates that salmon can detect the unique pheromones of their local population and related individuals, and often choose to associate accordingly (Quinn and Bu sack 1985;Quinn and Hara 1986;Winberg and Ols en 1992;Courtenay et al 1997;Ols en et al 2004;Fraser et al 2005). Thus, while the phero mone hypothesis proposed originally by Nordeng (1971Nordeng ( , 1977 for homing has fallen out of favour as a holistic framework based on a lack of evi dence (e.g.…”
Section: Stock-specific Sortingmentioning
confidence: 99%
“…These studies provide reliable evidence for kin recognition and kin preference both under laboratory and semi-field conditions. However, more generally, difficulties exist in detecting kinship in fish shoals in the wild (see Krause et al, 2000 for a review, Gerlach et al, 2001;Russell et al, 2004;Fraser et al, 2005) because there are a number of methodological issues which complicate the conclusions that can be drawn from them. Early studies (Avise and Shapiro, 1986;Naish et al, 1993;Peuhkuri and Seppa, 1998) may not have used sufficiently informative genetic markers to demonstrate that more kin were found within shoals than expected by chance.…”
Section: Introductionmentioning
confidence: 99%
“…Another problem of studying free-ranging shoals is that it is necessary to capture an entire shoal to be able to draw firm statistically testable conclusions regarding its size and composition (Krause et al, 2000). This has been an issue in several recent studies that either find no kin association (Herbinger et al, 1997), or do suggest that kin association occurs (Gerlach et al, 2001;Fraser et al, 2005).…”
Section: Introductionmentioning
confidence: 99%